Clinical, MRI and arthroscopic correlation in anterior and posterior shoulder instability - Joshi, Utkarsha Pradeep; Puri, Subhash (International Journal of Research in Medical Sciences, 2017)
Background:The peculiar anatomy of shoulder puts the glenohumeral joint at a great risk of instability, which poses a challenge for management. Clinical examination is not always accurate. MRI and arthroscopy are hence used to aid the diagnosis. The study aimed to compare and correlate clinical and Magnetic Resonance Imaging (MRI) in cases of anterior and posterior shoulder instability against the arthroscopic confirmation of the diagnosis, which is considered gold standard. Methods:A prospective study of 30 patients of shoulder instability (either anterior or posterior) was carried out, including both sexes and all age groups. The patients were first examined clinically, followed by 1.5 tesla MRI scan and finally arthroscopically. The findings of diagnostic arthroscopy were correlated with clinical & MRI findings. A definitive procedure to treat the pathology was then performed as per requirements. Sensitivity, specificity, positive predictive value, negative predictive value and overall accuracy of clinical and MRI findings was calculated to correlate with arthroscopic findings. Results:Clinical diagnostic tests and MRI had a significant statistic correlation (P <0.05) with various lesions responsible for instability. Diagnostic accuracy of MRI was considerably higher in comparison to clinical examination for both anterior (90% vs. 86.67%) and posterior (96.67% vs. 93.33%) shoulder instability. Conclusion:By obtaining correlation between clinical examination, MRI scan and arthroscopy for anterior and posterior shoulder instability, we conclude that MRI can give a better diagnosis of the pathology in comparison to clinical examination.